TRENDS IN DEVELOPMENT OF TRADE RELATIONS BETWEEN RUSSIA AND ASEAN COUNTRIES - Q. Th. Nguyen; K. M. Banar; Ia. S. Potapova (Вестник университета)
The perspective of development of trade relations between the Russian Federation and the countries of the Association of Southeast Asian Nations has been considered. The following projects: transport (“Russian Railways” OJSC with Indonesia; PJSC “Gazprom” projects, the South China Sea; “Petros” company projects), as well as the “East Siberia-Pacific Ocean” oil pipeline project have been considered. The import and export of Russia with some of the Association of Southeast Asian Nations countries for today and over the past ten years have been analysed. The prospect of a comprehensive association between Association of Southeast Asian Nations and the Eurasian Economic Union has been proposed. The most substantial and significant moments in maintaining the data of trade relations between countries have been highlighted. The possible reasons for the lack of large-scale and strong ties in some areas of activity between the Russian Federation and the Association of Southeast Asian Nations have been revealed, various options for creating and supporting mutually beneficial trade relations also have been offered.